Brain Metastasis from Breast Cancer in a Male Patient - Bee Chen Lua; Wan Zainira Wan Zain; Kok Bing Nelson Yap; Andee Dzulkarnaen Zakaria; Firdaus Hayati (2020)
Male breast cancer is a rare disease and has contributed to <1% of all cancers in the male population. Delay in diagnosis is common, due to its rarity and lack of awareness of the disease among the male patient and physicians. Most cases were detected at an advanced stage and up to 30% of them were diagnosed with metastasis on the initial presentation. The authors presented a case of a 60-yearold man who presented with seizure and right hemiparesis. In addition, he also has left breast mass for one year. Computed tomography of the brain showed a left frontal intra-axial brain lesion and biopsy of the breast lesion confirmed triple-negative invasive breast cancer. He was planned for whole-brain radiotherapy, however, he succumbed prior to the treatment.